The Face of Indonesian Accounting in the Frame of Local Culture: A Literature Review - Gunibala, Zakir Yusuf; Maharani, Maharani (Universitas Katolik Soegijapranata Semarang, 2024)
This study explores and reviews a number of articles on the topic of local culture accounting to map out relevant research opportunities in the future. Content analysis was used as an approach to interpret each article reviewed. Content analysis contains several aspects, including the type of research, data collection instruments and data analysis methods. This study reveals that research on the topic of Indonesian local culture accounting is mostly researched using qualitative methods. Based on these findings, it provides an opportunity for Indonesian local culture accounting research to be studied using quantitative and experimental methods, because it is still very rarely done. In addition, other findings show three topics of Indonesian local cultural accounting research that are often researched are related to accounting practices, fraud and accounting information systems. Then from the year of publication, the most research with related topics was published in 2023. To the best of the researchers' knowledge, this is the first study to review and analyze articles on the topic of Indonesian local culture accounting. This research makes a significant contribution to the understanding of the relationship between local culture and accounting practices in Indonesia. It also paves the way for further research that is more specific and contextualized, and offers guidance for accounting practitioners to understand the importance of considering cultural aspects in the application of accounting principles.